Gambling Addiction - Christine Wilcox
Gambling addiction costs American businesses $40 billion in lost wages and insurance claims each year. Through objective overviews, primary sources, and full color illustrations this title examines What is Gambling Addiction? Why Do People Become Addicted to Gambling? What Are the Costs of Gambling Addiction? Can Gambling Addiction Be Overcome?